Case Report: Peripheral blood T cells and inflammatory molecules in lung cancer patients with immune checkpoint inhibitor-induced thyroid dysfunction: Case studies and literature review - Marie, Mona A.; McCallen, Justin D.; Hamedi, Zahra S.; Naqash, Abdul Rafeh; Hoffman, Alexander; Atwell, Druid; Amara, Suneetha; Muzaffar, Mahvish; Walker, Paul R.; Yang, Li V. (Frontiers in Oncology, 2022)
Immunotherapy has changed the paradigm of cancer treatment, yet immune checkpoint inhibitors (ICIs) such as PD-1/PD-L1 monoclonal antibodies may cause immune-related adverse events (irAEs) in some patients. In this report, two non-small cell lung cancer (NSCLC) patients treated with nivolumab presented with checkpoint inhibitor-induced thyroid dysfunction (CITD), followed by a second irAE of pneumonitis and intestinal perforation, respectively. Increases in peripheral CD8+ T cells correlated with the onset of CITD in the patients. Intriguingly, common inflammatory biomarkers, including C-reactive protein (CRP) and neutrophil/lymphocyte ratio (NLR), were not consistently increased during the onset of CITD but were substantially increased during the onset of pneumonitis and intestinal perforation irAEs. The observations suggest that unlike other irAEs such as pneumonitis, CRP levels and NLR were non-contributory in diagnosing CITD, whereas T cell expansion may be associated with immunotherapy-induced thyroiditis.